Fine structure of the gametes and spermiogenesis in Spiophanes uschakowi (Annelida: Spionidae) from the Sea of Japan, with comments on fertilization biology in broadcast-spawning spionids. (December 2018) - Radashevsky, Vasily I.; Yurchenko, Olga V.; Alexandrova, Yana N.
Highlights: We describe the structure of the oocytes and spermiogenesis of a polychaete. The oocytes are lentiform, with honey-combed envelope and 41–49 cortical alveoli. The spermatozoa are ect-aquasperm with a plate-like acrosome and five mitochondria. Small granules on egg surface are assumed to attract sperm (sperm chemotaxis). Cortical alveoli are suggested as place of penetration of spermatozoon into oocyte. Abstract: Spiophanes uschakowi is a common polychaete living in tubes in sandy sediments in shallow waters of the Sea of Japan. Females and males release their gametes into the water where fertilization and holopelagic, planktotrophic larval development occur. In females, oogenesis is intraovarian: vitellogenesis occurs when the oocytes grow in paired ovaries attached to genital blood vessels in fertile segments. The developed oocytes are accumulated in the coelomic cavity prior to spawning. The newly released oocytes are lentiform, 185–200 μm in diameter, with honey-combed envelopes 5–7 μm thick. Each oocyte has 41–49 cortical alveoli regularly arranged in a peripheral circle, a nucleus 80–83 μm in diameter, and a single nucleolus about 30 μm in diameter. In males, spermatogonia proliferate in testes and the rest of spermatogenesis occurs in the coelomic cavity. During spermiogenesis, the acrosomal vesicle migrates from the posterior to the anterior part of the spermatid. The spermatozoa are ect-aquasperm with a plate-like acrosome 0.58 ± 0.06 μm thick and 2.14 ± 0.13 μm in diameter, barrel-shaped nucleus 2.23 ± 0.13 μm long and 3.18 ± 0.13 μm in diameter, short midpiece 0.93 ± 0.09 μm long with five spherical mitochondria, two centrioles and one small lipid droplet, and a flagellum 62–63 μm long with 9 × 2 + 2 organization of microtubules. The acrosome is a complex heterogeneous structure with 4–6 subspherical apical bodies, and numerous small branched basal cisternae. The anterior end of the nucleus is truncate, while its posterior end has wide shallow depressions accommodating the mitochondria. The centrioles are situated in the center of the midpiece between mitochondria and oriented obliquely to each other. The structure of the gametes of broadcast-spawning spionids is reviewed and the roles of surface granules in species-specific attraction of sperm toward eggs by releasing chemical signals (sperm chemotaxis), and cortical alveoli as a place of penetration of spermatozoa into oocytes (micropyle) are suggested. The lentiform oocytes of Spiophanes spp. are unique among Spionidae by their shape, while spermatozoa are unique by their plate-like acrosomes.